Argumentation and Fiction: Types of overlaps and their functions - Sierra-Catalán, Guillermo (Informal Logic)

(untitled) (Informal Logic, 2021)
Argumentation and fiction are quite different types of communicative phenomena. However, overlaps between them happen to be very frequent. We can both fictionalize by means of argumentation and argue by means of fiction. The main goal of this paper is to analyse the different types of overlap that may arise between argumentation and fiction. In this paper, the defended hypothesis is that by considering who the “character” that is arguing is, we can get an exhaustive account of any possible overlap, as well as an explanation of the different functions that such overlaps can play.